Alawici – czciciele Słońca czy Boga Najwyższego? - Rzym, Magdalena (Annales Missiologici Posnanienses, 2023)
This article presents that numerous unorthodox syncretic groups, which are composed of the elements of various religions, and emerged from Islam over the centuries. Their distinguishing feature was the exaggerated cult of some personalities, generally Ali Ibn Abi Talib. One of these movements is the Alawis that plays an important political role in Syria nowadays. The originality of the Alawis’ worship and doctrine is expressed by the importance of the sun and the moon, among others things. The light is the essence of God and the sun or the moon is considered God’s dwelling.